Home Garden; an Approach for Household Food Security and Uplifting the Status of Rural Women: A Case Study of Saptari, Nepal - Sagar Bhandari; Pankaj Kumar Yadav; Sramika Rijal (Turkish Journal of Agriculture: Food Science and Technology)
Food security is one of the major global challenges of the twenty-first century. World population is expected to increase by one-third, between 2009 and 2050, and in Asia, crop yield is estimated to decline by 5 to 30% from 2050 onwards compared to 1990. It is high time to seek alternatives that can increase production utilizing existing resources ensuring food security. A home garden can be a viable and sustainable alternative in this regard; nevertheless, it is often neglected. Thus, this study aims to understand the role of the home garden in maintaining household food security and enhancing rural women’s status in Nepal. Two villages of Bishnupur rural municipality, namely, Bajitpur and Musharniya were selected as study sites. 78.6% of households in Bajitpur and 68.4% households in Musharniya were found to have a home garden where crops and livestock were organized in an integrated way. The home garden was found to maintain household food security, ensure food availability for most of the seasons, access of household members to food, its utilization, and stability in production. Furthermore, 66.67% and 58.33% of women sold surplus home garden products in Bajitpur and Musharniya respectively. This signifies the role of home gardening activities in uplifting the social and economic status and, farming knowledge of rural women in both villages. However, there is a lack of extension facilities and subsidies for the home garden to encourage farmers. Therefore, different models of home gardens should be developed and disseminated, prioritizing the integration of the scientific farming system with traditional knowledge for sustainable adoption of the home garden in Nepal.